Fetomaternal Outcome Under Subarachnoid Block for Elective Caesarean Section - Sana Fatima, Syed Zia Haider, Muhammad Taqi, Kainat Khalid, Muhammad Mohsin Aftab, Sana Haseeb Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thecaesarean section (C/Section) births are escalating continuously. Foetal and Maternal outcome parameters might fluctuate under subarachnoid block. So, this investigation was delineated referring to fetomaternal outcome as Subarachnoid block was routinely employed for operative delivery in our institution. Objective: This study was conducted to determine fetomaternal outcome of neonatal and Maternal wellbeing in parturient undergoing elective caesarean section employing Subarachnoid block. Methodology: A Descriptive, cross sectional study employing Non-Probability Convenient Sampling was organized in Department of Obstetrics and Gynaecology, at a Tertiary Care Hospital at Lahore-Pakistan.240 parturients of 15 to 40 years of age were scrutinised for study. The study was of six months starting from August 2021 till January 2022. Results: TheNeonatal outcome was recorded as 1minute Apgar score of ≥7 was 233(97.1%) and <7 was 7(2.9), APGAR score at 5minutes of ≥8 was 237(98.7) and <8 was 3(1.3), Need for Neonatal ICU admissions was 5(2.09), Neonatal hypoglycaemia was 13(5.4). Maternal outcome was taken as Post operative nausea vomiting/PONV 8(3.3), Headache 25(10.4), Back pain 16(6.7), adult ICU admission 7(2.9), Length of Post op stay of ≤4 days 178(74.2) and >4 62(25.8). Conclusion: APGAR Score at 1 minute & 5 minutes was significantly high in parturients receiving Subarachnoid block for elective caesarean section. Keywords: APGAR score, Elective Operative Delivery, Foetal outcome, Maternal outcome, Subarachnoid block